Copyright Protection of Song in the form of Barcode in Spotify Application for Commercial Purposes - Inge Dwisvimiar; Fasya Mardhatillah Adani; Anne Gunawati (Faculty of Law, Andalas University, 2022)
The current development in digitalization has facilitated better human life, including enjoying the work of art, especially songs. One of the development is the Spotify application service. The application has made it easier to enjoy of work of song. Even though the song and music works have been protected in the Copywrite Law, the development has also caused the rise of copywriting violations. This article explores the legal protection for the Spotify application for song copyrighted works in the form of a barcode on the Spotify application for commercial purposes and the legal settlement regarding song copyrighted works in the form of a barcode on the Spotify application for commercial purposes. The research applied normative legal research with the statute, conceptual, and case study approach. The data collected are secondary data and primary which collected from library studies and field studies and analyzed descriptively and qualitatively. The study concludes that in practice legal protection in song and/or music copyrighted works can not be claimed and can not be protected because there is no recording of the results modified into acrylic products. Royalties can not be paid to creators and/or copyright holders though the infringement has been done and it has violated both moral rights and economic rights. Legal settlements cannot be completed through Article 95 of the Copyrights Law because there has been no official report by the aggrieved party, namely the creator and copyright holder, to the Spotify application.